The Role of Prophylactic Cranial Irradiation in Patients With Non-small Cell Lung Cancer: An Updated Systematic Review and Meta-Analysis - Liu, Lipin; Zhao, Ting; Zhong, Qiuzi; Cui, Jian; Xiu, Xia; Li, Gaofeng (Frontiers in Oncology, 2020)
Background: The purpose of this study was to reevaluate the efficacy of prophylactic cranial irradiation (PCI) in non-small cell lung cancer (NSCLC) with the most recent published data and to identify subgroups who may be more likely to gain benefit from PCI. Methods: We searched PubMed, Embase and Cochrane databases for randomized trials comparing PCI with non-PCI in NSCLC patients. We pooled the data and compared brain metastasis (BM) and overall survival (OS) between PCI group and non-PCI group. Results: Seven studies including 1462 patients were eligible for the current meta-analysis. Compared to non-PCI group, PCI group showed decreased BM (RR=0.37, 95% CI: 0.26–0.52) but similar OS (HR=1.01, 95% CI: 0.87–1.22). In subgroup analyses of BM, PCI decreased BM for subgroups by pathology (squamous cell carcinoma or non- squamous cell carcinoma) and local treatment modality (surgery or no surgery). However, PCI failed to reduce BM for patients with poor performance status (WHO 2-3). The incidence of PCI related toxicities was low and PCI was well tolerated by the majority of NSCLC. Low grade neurocognitive function (NCF) decline was reported in NAVLT study and greater deterioration in immediate and delayed recall was reported in RTOG 0214. No significant difference in quality of life (QOL) with PCI was reported. Conclusion: PCI reduces the incidence of BM except for patients with poor performance status. However, PCI fails to prolong OS significantly for NSCLC. An individual patient data meta-analysis may identify patients that could achieve OS prolongation with PCI.